The Motley Fool investment guide for teens : eight steps to having more money than your parents ever dreamed of - Gardner, David, 1966-; Gardner, Tom, 1968-; Maranjian, Selena (Fireside, 2002)
A guide to becoming financially independent with tips on saving and investing.